EXPLORING SAUDI REASONS FOR ECONOMIC REFORMS AND NEED TO STUDY THE SOCIAL IMPACT FOR ITS SUCCESS - Masood Ahmed (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Many countries are raising questions about the intentions behind Saudi reforms. The low oil prices in 2008-09 were the awakening call for Saudis, and later in 2014, it became the reason to look for an economy that is less dependent on oil. The article studies the initiated social reforms and the social impact of foreign cultural activities. It scrutinizes Saudi society under the social exchange theory and looks for the positive and negative effects of cultural exchanges. The paper also considers the COVID-19 situation in KSA as it has broken the chain of cultural events planned all over the country to promote tourism and improve the image of KSA.